Tinjauan Hukum Islam terhadap Budaya Cocok Weton dalam Perkawinan - Ustikorini, Lina; Ishaq, Zamroni (HOKI : Journal of Islamic Family Law, 2023)
Marriage is a relationship between two humans, namely men and women in fulfilling religious orders by living a family life in a household and aims to form a peaceful and harmonious community life. In practice, marriages are often carried out with various considerations, one of which is the weton consideration. Therefore, this research wants to examine how awareness of Islamic law regarding cultural practices that are suitable for weton in marriage in Sumur Geneng Village, Jenu District, Tuban Regency. Data collection methods used in this research are interviews, documentation, and observation. In this study, the data obtained directly from the research, namely primary data obtained from interviews and secondary data obtained from books or library materials, documentation that describes the condition of the people of Sumur Geneng Village, Jenu District, Tuban Regency. From the results of this study, it is found that people's understanding of the culture that is suitable for weton is actually only an endeavor, and reduces mere doubts. The calculation of the proper weton does not conflict with Islamic law because it is implied in the Al-Qur'an and the hadith of the Prophet Muhammad and is in accordance with the principles of Islamic law. Apart from that, the calculation of the weton of the prospective bride and groom is actually part of the endeavor, everything is up to His irodrat square.